Perancangan Desain UI/UX Sistem Akademik Di SMKN 8 Palembang Menggunakan Metode Lean UX - Suada, Wardha; Putra, M. Soekarno; Syakti, Firamon; Marlindawati, Marlindawati (Jurnal Ilmiah Media Sisfo, 2025)
The design of the academic information system at SMK Negeri 8 Palembang utilizes the Lean UX method to optimize user interface (UI) and user experience (UX). This study aims to solve inefficiencies in academic data management, prevent duplication, and reduce input errors commonly found in manual systems. The research process involved assumption declaration, development of a Minimum Viable Product (MVP) via Figma, experimentation using Maze, and usability evaluation through the System Usability Scale (SUS). Usability tests showed high completion rates, and the SUS score averaged 80.3, indicating excellent system acceptability. The results demonstrate that the developed UI/UX design offers an intuitive, efficient, and user-centered experience for students, teachers, and staff. This research contributes to digital transformation efforts in vocational education, providing a usable reference for the future implementation of web-based academic information systems. Keywords: lean ux, academic information system, ui/ux design, usability testing, vocational school